Human lymphocyte antigen CD38 catalyzes the production of cyclic ADP-ribose. - Summerhill, R; Jackson, D; Galione, A (1993)
The human lymphocyte antigen CD38 has been shown to share sequence homology with ADP-ribosyl cyclase, the enzyme that catalyzes the conversion of NAD+ to cyclic ADP-ribose (cADPR), a potent Ca(2+)-mobilizing agent. In this study COS1 cells from African Green Monkey kidney were transiently transfected with CD38 cDNA, inducing expression of authentic CD38 on the cell surface. We demonstrate that CD38 expressed in this manner can convert NAD+ to cADPR in the extracellular medium as assessed by Ca2+ release from sea-urchin egg microsomes.